2002
DOI: 10.1111/j.1365-2621.2002.tb08881.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Sensory Properties of Corn Tortillas Made from Nixtamalized Corn Flour Fortified with Spent Soymilk Residue (okara)

Abstract: The chemical study of okara composition and a sensory evaluation study were conducted to determine the effect of okara supplementation on certain physical, chemical and sensory properties of corn tortilla. Dried okara was added at the level of 5, 10, 15, 20, and 25% to nixtamalized corn flour. Due to flavor, enriched tortillas at levels higher than 10% of okara were not accepted. At 10% of okara supplement, lysine and tryptophan content in tortilla were increased from 56 and 70% of FAO profile to 93 and 92% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 9 publications
1
36
0
7
Order By: Relevance
“…Stanojevic et al, (2012) reported that the main protein found in okara is glycinin (11S protein), whose peptides contain cysteine and methionine residues (Murphy, 2008). Waliszewski et al (2002) verified the presence of the following antioxidative amino acids in okara: cysteine (12.5 g/kg protein), methionine (10.6 g/kg protein), tyrosine (34.3 g/kg protein), phenylalanine (48.4 g/kg protein) and tryptophan (11.4 g/kg protein). Thus the presence or absence of such amino acids in the peptides would affect the antioxidant activity of the hydrolysate.…”
Section: Antioxidant Activitymentioning
confidence: 76%
“…Stanojevic et al, (2012) reported that the main protein found in okara is glycinin (11S protein), whose peptides contain cysteine and methionine residues (Murphy, 2008). Waliszewski et al (2002) verified the presence of the following antioxidative amino acids in okara: cysteine (12.5 g/kg protein), methionine (10.6 g/kg protein), tyrosine (34.3 g/kg protein), phenylalanine (48.4 g/kg protein) and tryptophan (11.4 g/kg protein). Thus the presence or absence of such amino acids in the peptides would affect the antioxidant activity of the hydrolysate.…”
Section: Antioxidant Activitymentioning
confidence: 76%
“…Despite the high nutritional and excellent functional properties (emulsification, foaming, and binding properties) of okara and its potential for application in food products, the most common use of this by-product is in the manufacture of animal feed (PINTO; CASTRO, 2008). Okara has been used to partially replace wheat flour, cassava starch, corn flour, and soy flour (BOWLES; DEMIATE, 2006;GRIZOTTO et al, 2010;APLEVICZ;DEMIATE, 2007;RINALDI;NG;BENNINK, 2000;WALISZEWSKI;PARDIO;CARREON, 2002). The use of okara as a fat replacer in meat products is still in the experimental stage (TURHAN; TEMIZ; SAGIR, 2007).…”
Section: Sensory Analysismentioning
confidence: 99%
“…A suplementação de produtos alimentícios com okara foi relatada em 2002, por WALISZEWSKI, PARDIO & CARREON [31]. Os autores realizaram uma avaliação química e sensorial de okara, incluindo um perfil da composição em aminoácidos, e foram incorporadas porcentagens de 5, 10, 15, 20 e 25% deste subproduto em Tortillas.…”
Section: -Introduçãounclassified